A rare case of Dandy-Walker syndrome in the 12-year-old girl - Deepak Khandelwal; Dhiraj Kumar; Namita Kalra; Rishi Tyagi; Amit Khatri; Sunil Kumar (Wolters Kluwer Medknow Publications, 2020)
Dandy-Walker syndrome (DWS) is a rare congenital cystic malformation of the posterior cranial fossa. Patients show signs and symptoms of complex clinical manifestations, ranging from cranial nerve and cerebellar dysfunctions to extracranial abnormalities, which may pose challenges in dental management. This article represents a rare case of a 12-year-old girl with DWS along with the involvement of the oral cavity.